2007
DOI: 10.1039/b615486g
|View full text |Cite
|
Sign up to set email alerts
|

A cell-laden microfluidic hydrogel

Abstract: The encapsulation of mammalian cells within the bulk material of microfluidic channels may be beneficial for applications ranging from tissue engineering to cell-based diagnostic assays. In this work, we present a technique for fabricating microfluidic channels from cell-laden agarose hydrogels. Using standard soft lithographic techniques, molten agarose was molded against a SU-8 patterned silicon wafer. To generate sealed and water-tight microfluidic channels, the surface of the molded agarose was heated at 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
347
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(353 citation statements)
references
References 45 publications
1
347
2
2
Order By: Relevance
“…Previous studies in 2-D and 3-D culture work have used photolithographic techniques [31,[33][34][35], laminar flow [36,[49][50][51][52], and combinations thereof [32,53,54], to generate microarrays of photo-reactive polymers. Although these previous studies provide valuable insights into the effects of ECM signals on cell behavior, photolithographic techniques are typically limited to the use of photo-reactive polymers, and laminar flow is dimensionally limited to micro-scale materials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in 2-D and 3-D culture work have used photolithographic techniques [31,[33][34][35], laminar flow [36,[49][50][51][52], and combinations thereof [32,53,54], to generate microarrays of photo-reactive polymers. Although these previous studies provide valuable insights into the effects of ECM signals on cell behavior, photolithographic techniques are typically limited to the use of photo-reactive polymers, and laminar flow is dimensionally limited to micro-scale materials.…”
Section: Discussionmentioning
confidence: 99%
“…Such advances allow the introduction of spatially specific cues in hydrogels, making multicellular constructs, either through co-cultures or multilineage differentiation, a possibility [16][17][18] . Spatial patterning of hydrogels also provides an additional tool for the development of high-throughput screening technology for the rapid investigation of cell-material interactions [19][20][21][22] .…”
Section: Static Hydrogels That Mimic Biophysical Cuesmentioning
confidence: 99%
“…Since then, we have extended their approach to ECM gels using chaotropes and other perturbants (such as glycerol for type I collagen), and others have shown that silk and agarose gels are also amenable to bonding. 4,23,38 By iteratively molding, stacking, and bonding thin layers of alginate, Zheng et al 58 recently showed that three-dimensional interconnected microscale networks could be constructed within gels.…”
Section: Micromoldingmentioning
confidence: 99%